2007
DOI: 10.1113/expphysiol.2007.038851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin‐converting enzyme inhibition on skeletal muscle oxidative function and exercise capacity in streptozotocin‐induced diabetic rats

Abstract: Since exercise capacity is related to the mitochondrial respiration rate in skeletal muscle and both parameters are potentially modulated by the onset of diabetes and by inhibition of the angiotensin-converting enzyme (ACE), we investigated whether skeletal muscle oxidative functions and exercise capacities are impaired in chronic streptozotocin-induced diabetic (STZ) rats and whether ACE inhibition could reverse such abnormalities. The ACE inhibitor perindopril (2 mg kg −1 day −1 ) was given for a period of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
(80 reference statements)
1
10
0
1
Order By: Relevance
“…Mitochondrial dysfunction might be a key factor in the ageing‐related decrease in skeletal muscle function. Indeed, mitochondria are the main energy producers in cells, and significant mitochondrial dysfunction leads to organ dysfunction (Fink, 2001; Rouyer et al 2007). In the present study, the use of main substrates allowed us to determine the mitochondrial respiratory chain complex activities precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction might be a key factor in the ageing‐related decrease in skeletal muscle function. Indeed, mitochondria are the main energy producers in cells, and significant mitochondrial dysfunction leads to organ dysfunction (Fink, 2001; Rouyer et al 2007). In the present study, the use of main substrates allowed us to determine the mitochondrial respiratory chain complex activities precisely.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, several studies reported decreased muscle mitochondrial metabolism and morphological disturbances in STZ‐treated rats, including decreased mitochondrial mass, increased number of disarrayed cristae and mitochondrial swelling, reduced matrix electron density and compromised activity of several Krebs Cycle enzymes [5–9]. Mitochondrial alterations associated with decreased function seem to be related with increased oxidative stress and damage within the muscle from hyperglycaemic subjects [9].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged ACE inhibition completely prevented the decreased skeletal muscle oxidative capacity expected in patients with chronic heart failure (10) and in rats with heart failure secondary to myocardial infarction (32,35). However, this protective effect of ACE inhibition remains controversial, and perindopril administration failed to restore muscle oxidative capacity and mitochondrial function in a rat model of heart failure induced by aortic stenosis (16) or in a rat model of type I diabetes (22). Taken together, these previous findings suggested that ACE inhibitors at best improve the mitochondrial dysfunction that characterizes skeletal muscle myopathy associated with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%